Asset-based lending - Suzanne H. Bijkerk; Casper G. de Vries (Center for Economic Studies and ifo Institute (CESifo), 2019)
Asset-based lending, the supply of loans based on floating collateral, is an important source of funding for small .rms. We analyze the effect of competition on asset-based loan markets on interest rate distributions and the mobility of small firms. Close monitoring of collateral by lenders results in an informational advantage for the incumbent lender and third-degree price discrimination. We find that adverse selection results in a unique equilibrium in which lenders randomize interest rates and firms switch lender with positive probability. Increased competition between lenders does not benefit firms through lower expected interest rates, neither does it improve their mobility.
Keywords: D53; D82; 330; asset-based lending; floating; collateral; adverse selection